Incidência e fatores preditores para candidemia em pacientes internados em Unidades de Terapia Intensiva de hospital terciário na região Centro-Oeste do Brasil - Santos, Hugo Dias Hoffmann (2017)
Candidemia, a hospital disease of the bloodstream, increases hospitalization time, raises hospital costs and increases the number of deaths. A cohort was conducted with patients hospitalized in intensive care and neonatal care units between 2014-2016 to assess the risk of developing candidemia and its predisposing factors. After the return of 44405 patient-daysthe study of 36 cases of candidemia was observed, being 17 in neonatal ICU and 19 in ICU. The main etiological agente of candidemia in patients hospitalized in the neonatal ICU was the C. parapsilosis complex and in adult ICUs it was C. albicans. The incidence of candidemia was statistically among urinary tract infections, but the candidemia ratio was statistically higher among patients admitted to the neonatal intensive care unit. By time adjustment, hospitalization for 20 days (RR = 11.18, 95% CI = 3.34-37.40), glycopeptide antibiotic therapy concomitant with parenteral nutrition (RR = 30.85, 95% CI = 4.70- 202,65) and use of fluconazole for more than 10 days (RR = 0.21, 95% CI = 0.10-0.48) behaved as predictors of candidemia. The risk of candidemia was similar between the ICU and neonatal, among the Candida species and higher among the patients who developed candiduria. Epidemiological data on candidemia were analyzed using cohorts, some, some performed a survival analysis, but there was na assessment of the risk for developing candidemia, ie the predisposing factors involved in the time between a hospitalization diagnosis, can help in better control of this important infection.